Shades of Communitas: A Study of Soft Skills Programs. (August 2019) - Fixsen, Alison; Ridge, Damien
In societies where neoliberal individualism prevails, communal experiences nevertheless remain crucial to human life. Drawing on participant data from a series of soft skills programs (SSPs) for Higher Education (HE) staff, we investigated SSP social worlds, their role in staff navigation in uncertain times and points of resistance within them. We found SSPs to be distinctly performative platforms, engaging actors in various self-care and entrepreneurial activities. A complex network of relationships was established via SSPs, as well as group effects akin to communitas, in "lighter" and "darker" forms. Incongruities of SSPs included gender imbalances and emotional management problems, while a mismatch between managerial attempts to create positive communitas and the reality of mounting workloads and job-cuts facing HE staff were noted in this study. SSPs may help counter organizational siloism, yet reflect the ambiguities within neoliberal culture and can deter staff from pursuing political modes of collective expression in the workplace.